Strategi Implementasi Kurikulum Integratif Berbasis Nilai Keislaman di Madrasah Ibtidaiyah - Suyitman, Suyitman; Basit, Abdul (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2026)
This study aims to describe teacher strategies in implementing an integrative curriculum based on Islamic values ​​at MIN 3 Cilacap and to outline the obstacles encountered and their solutions. This study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews with teachers, and documentation studies. To ensure the validity of the research data, technical triangulation was conducted. The results of the study indicate that the implementation of the integrative curriculum strategy is carried out through collaborative planning between teachers, integration of Islamic values ​​in teaching materials, optimization of the Pancasila and Rahmatan lil 'Alamin Student Profile Strengthening Project (P5-RA), and improvement of teacher competency. Obstacles faced include limited understanding of the integration concept, limited learning resources, and project implementation time. The solutions implemented include internal training, development of collaborative open modules, and integration of P5-RA in learning themes. The implications of this study encourage madrasas to strengthen a collaborative culture and innovation in the integration of Islamic values.